Relationship between Allocation of Health Operational Assistance Funds and Achievement of Minimum Service Standards at Regional Technical Implementation Unit Health Centers in Konawe Islands Regency - Kaharuddin, Kaharuddin; Saafi, La Ode; Risky, Sartini (Magister Kesehatan Universitas Mandala Waluya, 2023)
Introduction :Based on data from the Report of the UPTD LadiantaPublic Health Center, most of the indicators for the health Minimum Service Standards that have been implemented by the UPTD LadiantaPublic Health Center have not reached the predetermined target of 100% (one hundred percent) such as health of both mother and child.The purpose of this study was to analyze the relationship between the allocation of health operational assistance fundsby achieving minimum service standards at UPTD Public Health CenterLansilowo and UPTD Public Health CenterLadianta in 2022 . Methods :This type of research is analytic using a cross sectional approach. The population of this research is the population of this research is all the staff of the UPTD of the LansilowoPublic Health Center, totaling 30 people andall staffUPTD Ladianta Public Health Centertotaled 30people . The sample is 53 people. The statistical analysis of the results used is the chi square test. Result:The results of the study showed that there was a relationshipThere is a relationship with the allocation of health operational assistance fundsby achieving minimum service standards for maternal and child health, health promotion, environmental health, nutrition and immunization at the UPTD LansilowoPublic Health Center and UPTD LadiantaPublic Health Center in 2022 . Conlusions:Public Health Centershould further improve communication between leaders as budget managers and program holders, so that in managing the health operational assistance budget, the performance of health services for the community will increase.